MENENTUKAN MOMEN INERSIA BENDA BERBENTUK SEMBARANG MENGGUNAKAN PESAWAT NANOBADE - sunardi, sunardi; Walukow, Auldry F.; triwiyono, triwiyono (Universitas Cenderawasih, 2023)
The moment of inertia practicum in Physics learning in SMA/MA and equivalent is only carried out for objects with regular shapes and tends to be abandoned for objects with irregular shapes. The practicum for determining the moment of inertia of irregularly shaped objects tends to be abandoned due to the lack of adequate practicum tools. This study proposes a moment of inertia practicum tool called the Nanobade Plane which can be used to measure the moment of inertia of objects with regular shapes and irregular shapes. In the trial of the tool for measuring the moment of inertia (I) of a regular object in the form of a block with dimensions of length 14.83 cm, width 14.795 cm, thickness 2.05 cm and mass 257.92 g, the I value was obtained as much as 0.000929 kg m², while using the formula the I value was obtained as much as 0.000943 kg m². There is a difference in I of 0.000014 kg m² or an error of 1.48%. With the percentage error value, it can be stated that this practicum tool is suitable for use for moment of inertia experiments. Measurement of the moment of inertia of irregular objects using a tool was carried out on two different objects, namely a bottle filled with water and solid rubber, it turned out that the value of I for the bottle filled with water was 0.000929 kg m2, while I for solid rubber was 0.00038 kg m². With the discovery of this tool, the need for inertia moment practicums at the high school/vocational high school level and equivalent can be met. Compared to previous similar tools, this Nanobade Aircraft has a number of advantages such as being made from materials around us, easy to make, relatively affordable manufacturing costs, getting results close to accurate values, and can attract students' interest in learning.